2014
DOI: 10.1007/s00705-014-2124-1
|View full text |Cite
|
Sign up to set email alerts
|

The zoonotic potential of avian influenza viruses isolated from wild waterfowl in Zambia

Abstract: Whilst remarkable progress in elucidating the mechanisms governing interspecies transmission and pathogenicity of highly pathogenic avian influenza viruses (AIVs) have been made, similar studies focusing on low pathogenic AIVs isolated from the wild waterfowl reservoir are limited.We previously reported that two AIV strains (subtypes H6N2 and H3N8) isolated from wild waterfowl in Zambia harbored some amino acid residues preferentially associated with human influenza virus proteins (so-called human signatures) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The replication and transmission of H6N2 and H6N6 viruses were limited in SFP chicken in this study, although the pathological changes caused by H6N2 in chickens were reported in California 13 . Previous study showed that H6N2 isolates caused seroconversion in infected chickens, but no virus was recovered from the tissue samples, which suggested that the H6N2 strains replicated poorly and were nonpathogenic to chickens 52 . Our findings showed that the five H6 strains selected from different genotypes caused no clinical signs in any of the inoculated chickens, but the serological test results suggested that chickens in four groups have been infected despite limited recovery of inoculated viruses from the tissue samples.…”
Section: Pathogenicity In Micementioning
confidence: 95%
“…The replication and transmission of H6N2 and H6N6 viruses were limited in SFP chicken in this study, although the pathological changes caused by H6N2 in chickens were reported in California 13 . Previous study showed that H6N2 isolates caused seroconversion in infected chickens, but no virus was recovered from the tissue samples, which suggested that the H6N2 strains replicated poorly and were nonpathogenic to chickens 52 . Our findings showed that the five H6 strains selected from different genotypes caused no clinical signs in any of the inoculated chickens, but the serological test results suggested that chickens in four groups have been infected despite limited recovery of inoculated viruses from the tissue samples.…”
Section: Pathogenicity In Micementioning
confidence: 95%
“…Cleaveland et al ( 2007 ), in their assessment of the risk of disease emergence by taxa, found that the relative risk of disease emergence was highest for bats, followed closely by primates, then ungulates and rodents. There have been surprisingly few studies of the connection between hunting of birds or other vertebrates and EIDs, especially in Africa, but surveillance for zoonotic pathogens in African birds is strongly needed (e.g., for avian infl uenza tracking see Simulundu et al 2011Simulundu et al , 2014.…”
Section: Bushmeat As a Source Of Zoonotic Diseases In Sub-saharan Africamentioning
confidence: 99%
“…Human antibodies against the AIV-H13 subtype, previously detected in Asia, have been scarcely reported [ 9 ]. More frequent are cases of seropositivity to the AIV-H11 subtype that, as experimentally shown, has zoonotic potential to mammalian hosts [ 71 ]. Serological evidence of H11 infections have been previously reported in poultry workers [ 32 , 33 , 41 ] and—interestingly—in humans frequently exposed to wild birds for occupational or recreational purposes [ 69 , 72 ].…”
Section: Discussionmentioning
confidence: 99%